2020
DOI: 10.1089/vbz.2019.2519
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Epidemiological Study of Selected Zoonotic and Abortifacient Pathogens in Cattle at a Wildlife-Livestock Interface in South Africa

Abstract: A cross sectional sero-epidemiological study was conducted on cattle in a communal farming area adjacent to Kruger National Park at a wildlife-livestock interface in South Africa. A total of 184 cattle were screened for exposure to 5 abortifacient or zoonotic pathogens, namely Coxiella burnetii, Toxoplasma gondii, Chlamydophila abortus, Neospora caninum, and Rift Valley fever virus (RVFV) using enzyme-linked immunosorbent assays. In addition, the virus neutralization test was used to confirm the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 75 publications
1
16
2
Order By: Relevance
“…Further, the predominantly mixed infections observed (Figure -1) were leptospirosis and Q fever (34.5%) followed by all three infections (4.87%); toxoplasmosis and leptospirosis (3.54%); and toxoplasmosis and Q fever (2.21%), which are corroborated with the reported data by various researchers in different studies. Adesiyun et al [27] observed the seroprevalence of 38% and 33% for C. burnetii and T. gondii, respectively, while studying the epidemiology of the cattle for exposure to different abortifacient zoonotic pathogens. In contrast, Sekovanić et al [28] reported a prevalence of 5% and 6% for Q fever and leptospirosis, respectively, without a single positive of brucellosis in cattle during 5 years of study in Croatia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the predominantly mixed infections observed (Figure -1) were leptospirosis and Q fever (34.5%) followed by all three infections (4.87%); toxoplasmosis and leptospirosis (3.54%); and toxoplasmosis and Q fever (2.21%), which are corroborated with the reported data by various researchers in different studies. Adesiyun et al [27] observed the seroprevalence of 38% and 33% for C. burnetii and T. gondii, respectively, while studying the epidemiology of the cattle for exposure to different abortifacient zoonotic pathogens. In contrast, Sekovanić et al [28] reported a prevalence of 5% and 6% for Q fever and leptospirosis, respectively, without a single positive of brucellosis in cattle during 5 years of study in Croatia.…”
Section: Resultsmentioning
confidence: 99%
“…Adesiyun et al . [ 27 ] observed the seroprevalence of 38% and 33% for C. burnetii and T. gondii , respectively, while studying the epidemiology of the cattle for exposure to different abortifacient zoonotic pathogens. In contrast, Sekovanić et al .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in South Africa, a seroprevalence of 61% was found in people working with cattle [ 35 ]. The same cattle population had a seroprevalence of 38% [ 36 ]. Risk to the general population should also be taken into account as the farming animals roam on roads and private properties.…”
Section: Discussionmentioning
confidence: 99%
“…One study on humans, livestock and wildlife found that the incidence of Q fever in cattle and wildlife was associated with arthropod vectors [22]. Another cross sectional sero-epidemiological study conducted in South Africa concluded higher risk of zoonotic transmission and economic loss was associated with the livestock-wildlife interface [23] and this has been supported by a number of studies across Africa [21,24,25].…”
Section: Introductionmentioning
confidence: 95%